Changes in inferior vena cava area represent a more sensitive metric than changes in filling pressures during experimental manipulation of intravascular volume and tone. (11th January 2022) - Ivey‐Miranda, Juan B.; Wetterling, Friedrich; Gaul, Robert; Sheridan, Stephen; Asher, Jennifer L.; Rao, Veena S.; Maulion, Christopher; Mahoney, Devin; Mebazaa, Alexandre; Gray, Alastair P.; Burkhoff, Daniel; Cowie, Martin R.; et al.
Abstract : Aims: Remote monitoring of pulmonary artery pressure has reduced heart failure (HF) hospitalizations in chronic HF as elevation of pulmonary artery pressure provides information that can guide treatment. The venous system is characterized by high capacitance, thus substantial increases in intravascular volume can occur before filling pressures increase. The inferior vena cava (IVC) is a highly compliant venous conduit and thus a candidate for early detection of change in intravascular volume. We aimed to compare IVC cross‐sectional area using a novel sensor with cardiac filling pressures during experimental manipulation of volume status, vascular tone, and cardiac function. Methods and results: Experiments were conducted in sheep to manipulate volume status (colloid infusion), vascular tone (nitroglycerin infusion) and cardiac function (rapid cardiac pacing). A wireless implantable IVC sensor was validated ex‐vivo and in‐vivo, and then used to measure the cross‐sectional area of the IVC. Right‐ and left‐sided cardiac filling pressures were obtained via right heart catheterization. The IVC sensor provided highly accurate and precise measurements of cross‐sectional area in ex‐vivo and in‐vivo validation. IVC area changes were more sensitive than the corresponding changes in cardiac filling pressures during colloid infusion ( p  < 0.001), vasodilatation ( p  < 0.001) and cardiac dysfunction induced by rapid pacing ( p  ≤ 0.02). Conclusions: Inferior vena cava area can be remotely and accurately measured in real time with a wireless implantable sensor. Changes in IVC area are more sensitive than corresponding changes in filling pressures following experimental volume loading and fluid redistribution. Additional research is warranted to understand if remote monitoring of the IVC may have advantages over pressure‐based monitors in HF. Abstract : A wireless inferior vena cava (IVC) sensor was implanted in sheep followed by experiments to manipulate volume status, vascular tone, and cardiac function. The IVC sensor provided accurate measurements of cross‐sectional area. IVC area changes were more sensitive than the corresponding changes in cardiac filling pressures during manipulation of volume status, vascular tone, and cardiac function. PAP, mean pulmonary artery pressure; RAP, right atrial pressure.